2018
DOI: 10.1016/j.virol.2018.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus 16 E6 modulates the expression of miR-496 in oropharyngeal cancer

Abstract: Human papillomavirus (HPV), notably type 16, is a risk factor for up to 75% of oropharyngeal squamous cell carcinomas (SCC). It has been demonstrated that small non-coding RNAs known as microRNAs play a vital role in the cellular transformation process. In this study, we used an LNA array to further investigate the impact of HPV16 on the expression of microRNAs in oropharyngeal (tonsillar) cancer. A number of miRNAs were found to be deregulated, with miR-496 showing a four-fold decrease. Over-expression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Previous studies have indicated that miR-496 is associated with several human pathological changes, including oropharyngeal cancer (27), cerebral ischemia/reperfusion injury (28), type 2 diabetes mellitus and obesity (29), and osteogenesis of human bone marrow (30). These findings suggest that miR-496 serves as a suppressor in human pathological changes, which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have indicated that miR-496 is associated with several human pathological changes, including oropharyngeal cancer (27), cerebral ischemia/reperfusion injury (28), type 2 diabetes mellitus and obesity (29), and osteogenesis of human bone marrow (30). These findings suggest that miR-496 serves as a suppressor in human pathological changes, which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…MiRNAs can target or control the expression of tumor-related genes, thereby promoting or inhibiting the occurrence and progression of tumor (Sun et al, 2018 (Dmitriev et al, 2013;Lu et al, 2018;Mason et al, 2018). A study reported long noncoding RNA-DANCR contributes to lung adenocarcinoma progression by sponging miR-496 to modulate mTOR expression (Lu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-496 was recently found to be a novel mammalian target of rapamycin (mTOR) regulator associated with aging-relevance (Rubie et al, 2016). Besides, miR-496 level has been reported to be deregulated in several diseases, such as facioscapulohumeral muscular dystrophy, age-related diseases, and tumor progression (Dmitriev et al, 2013;Lu et al, 2018;Mason et al, 2018). A study reported long noncoding RNA-DANCR contributes to lung adenocarcinoma progression by sponging miR-496 to modulate mTOR expression (Lu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The limited associations observed between IHC markers and HNSCC are consistent with the research conducted by Hashmi et al (2018) [ 19 ]. The function of miRNAs, HPV association, and genetic variation have been explored in several HNSCC-related studies, Sais et al (2018), Momi et al (2014), Miller et al (2015), and Wilkins et al (2018) [ 20 - 23 ].…”
Section: Discussionmentioning
confidence: 99%